Modern Education and Change in Mindset and Behavior of Saminist (Historical Perspectives of Saminist Community in Jepang Hamlet, Margomulyo Village, Margomulyo District, Bojonegoro Regency) - Sunarjan, YYFR.; Setyowati, Dewi Liesnoor; Sudirman, Berlian Surya Rimbani (International Journal of Psychosocial Rehabilitation, 2020)
Saminist is a group of people who are traditionally upholding the values of ancestral teachings, but in its development Saminist young generation is willing to receive formal education that brings new values and enhanching the Wellfare.. The purpose of this study is to analyze the poverty, mind and behavior of Saminist teenagers in formal schools. The research employed qualitative method, with a historical perspective. The location of this research was Jepang Hamlet, Margomulyo Village, Margomulyo District, Bojonegoro Regency and also Junior High School Margomulyo. The informants of this study are 9 saminist adolescents attending Junior High School Margomulyo, 6 families of Sedulur Sikep adolscent, 6 saminist schoolmates, 2 teachers and Sedulur Sikep ancestor. The techniques of data collection are in-depth interviews, observation and documentation. The results showed that acculturation of Sedulur Sikep adolescents’ mindset in formal school include (1) acceptance of competition; (2) acceptance of sanction in the school. In addition, the behaviour acculturation of saminist adolescent in formal school include (1) using Javanese Ngoko and Indonesian language; (2) using transportation and communication technology; (3) participate in Islamic learning. Saminist have changed in thinking and behavior, but they don’t leave the beliefs and values of the Sedulur Sikep teaching that have been planted for generations.